Quantitative EEG in Depression and Posttraumatic Stress Disorder - Begić, Dražen; Jokić-Begić, Nataša (2010)
A qEEG was adminestered with 30 patients with depression, 34 patients with PTSD and 40 healthy subjects. Results indicate a difference between depression and the PTSD in the delta rhythms (especially over the frontal and central regions). Results from this study were compared and interpreted in the context of the neurotransmitter and neuroradiological studies of depression and PTSD.
Projekt MZOS
ENG